Reproducibility of the Vivatmopro measurements for exhaled nitric oxide values - Amaral, Rita (2020)
Portable monitoring devices allow fraction exhaled nitric oxide (FeNO) measurements outside clinical settings. However, the reproducibility of the new portable device Vivatmo pro is not yet fully established. In this study, we aimed to assess the reproducibility of this device for FeNO measurements.